PENGARUH KEBIJAKAN TATA CARA PEMBUATAN DAN PELAPORAN FAKTUR PAJAK BERBENTUK ELEKTRONIK TERHADAP PENGUSAHA KENA PAJAK DENGAN TINGKAT PEMAHAMAN SEBAGAI VARIABEL MODERASI (Studi Empiris pada KPP Pratama Pondok Aren) - Ade Auliya Putri; Lely Suryani (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2017)
The purpose of this research is to know and analyze the influence of the policy of procedure of making and reporting tax invoice electronic form to taxable entrepreneur with level of understanding as moderation variable. This study used primary data in the form of questionnaires distributed in KPP Pratama Pondok Aren. Data processing using Statistical Product and Service Solution for Windows version 22 (SPSS version 22). The analysis method used is Data Quality Test (Validity Test, Realibility & Multicolinearity Test), Multiple Linear Regression Test, Correlation Coefficient Test, Coefficient of Determination Test, F Test and T Test, Absolute Difference Test. Based on the results of multiple regression test and multiple moderation regression, partially the policy of making procedure has no effect on the taxable entrepreneur but the reporting of tax invoice in the form of electronics has an effect  to the taxable entrepreneur. While the procedures for making and reporting tax invoices in the form of electronic, influence the taxable entrepreneurs. While simultaneously the procedure of manufacture and reporting tax invoice in the form of electronics do not affect the taxable entrepreneurs with the level of understanding as a moderation variable..